A novel layered topology of auxetic materials based on the tetrachiral honeycomb microstructure. (5th October 2019) - Auricchio, Ferdinando; Bacigalupo, Andrea; Gambarotta, Luigi; Lepidi, Marco; Morganti, Simone; Vadalà, Francesca
Abstract: Microstructured honeycomb materials may exhibit exotic, extreme and tailorable mechanical properties, suited for innovative technological applications in a variety of modern engineering fields. The paper is focused on analysing the directional auxeticity of tetrachiral materials, through analytical, numerical and experimental methods. Theoretical predictions about the global elastic properties have been successfully validated by performing tensile laboratory tests on tetrachiral samples, realized with high precision 3D printing technologies. Inspired by the kinematic behaviour of the tetrachiral material, a newly-design bi-layered topology, referred to as bi-tetrachiral material, has been theoretically conceived and mechanically modelled. The novel topology virtuously exploits the mutual collaboration between two tetrachiral layers with opposite chiralities. The bi-tetrachiral material has been verified to outperform the tetrachiral material in terms of global Young modulus and, as major achievement, to exhibit a remarkable auxetic behaviour. Specifically, experimental results, confirmed by parametric analytical and computational analyses, have highlighted the effective possibility to attain strongly negative Poisson ratios, identified as a peculiar global elastic property of the novel bi-layered topology. Graphical abstract: Unlabelled Image Highlights: A novel layered topology of auxetic cellular materials based on the tetrachiral honeycomb microstructure, named bi-tetrachiral material, is proposed. The global elastic properties of 3D printed samples of the bi-tetrachiral material are experimentally identified from quasi-static tensile tests. Computational finite element models and beam lattice models efficiently reproduce the experimental response of the bi-tetrachiral material. The mutual collaboration of two tetrachiral layers with opposite chirality prevents the development of global angular strains under tensile loads. Parametric analyses show that Poisson ratios close to −1 are achievable by regulating the distance between the interlayer constraints.